2014
DOI: 10.1530/eje-14-0069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term GH replacement therapy on cardiovascular outcomes in isolated GH deficiency compared with multiple pituitary hormone deficiencies: a sub-analysis from the Dutch National Registry of Growth Hormone Treatment in Adults

Abstract: Objective: Isolated GH deficiency (IGHD) could provide a model to investigate the influence of GH deficiency per se and the effect of GH replacement therapy without the influence from other pituitary hormone deficiencies or their treatment. The aim of this study is to address the questions about differences between IGHD and multiple pituitary hormone deficiencies (MPHDs) in clinical presentation and in responsiveness to GH treatment. Design: A nationwide surveillance study was carried out to describe the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…GH has a pronounced lipolytic effect, particularly in abdominal fat [28]. Previous studies have shown that administration of rhGH could improve lipid profile in patients with GHD [29] and obese adults [30]. However, data in obese adolescents were limited and conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…GH has a pronounced lipolytic effect, particularly in abdominal fat [28]. Previous studies have shown that administration of rhGH could improve lipid profile in patients with GHD [29] and obese adults [30]. However, data in obese adolescents were limited and conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven studies were identified where the study aims were safety, morbidity, glucose metabolism, or adverse event (AE) reporting [18,19,24,27,28,31,34,35,37,39,41,42,49,59,62,66,71,82,85,89,91,92,96,97,102,105,107]. Fifteen studies reported the primary aim to be safety in general and 12 studies glucose metabolism, DM incidence or prevalence.…”
Section: Glucose Metabolism and Risk Of Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Eleven studies were identified that stated safety, vascular morbidity or mortality as the aim of the study [19,51,59,62,85,90,[96][97][98]102,109]. All studies were open label and the mean number of patient years was 3417, ranging from 804 to 69,056.…”
Section: Vascular Morbidity and Mortalitymentioning
confidence: 99%
“…• Check the hypothalamic-pituitary-adrenal axis and replace if necessary No increased malignancy rates (41) or malignancy-related mortality (42) were demonstrated on more recent studies.…”
Section: Box 3 Recommendations For Gh Replacement Treatmentmentioning
confidence: 99%